3D modeling and photogrammetric measurement procedure for architecture and industrial applications - Maarof, Ismail; Setan, Halim (2005)
Recent developments of digital camera in terms of size of Charged Couple Device (CCD) arrays and reduced costs are leading to their application to traditional as well as new photogrammetric surveying and mapping function. Digital cameras, intended to replace conventional film based mapping camera, are becoming available along with many smaller format digital camera capable of large-scale and precise measurement application. The development in digital photogrammetry technology is inline with the development in the computer and digital technologies. This paper introduces a new procedure for 3D modeling and photogrammetric measurement using low cost digital camera (Kodak DC 290 and Olympus) and Photomodeler Pro 5.0 software. The measurement and modeling results are presented in suitable forms (i.e. dimensional plan, graphic plan and 3D model visualization), based on the needs and specification of both architecture and industrial engineering disciplines. The resulted 3D model can be exported to other formats such Autocad drawing (*.dwg) and Rhinoceros file format (*.3dm). For verification, the measurement obtained was compared with tape, intersection measurement, actual plan and AXYZ Industrial Measurement System. The overall results show differences of 1.0mm-20.0mm and 0.1mm-04mm, indicating the suitability of the low cost photogrammetric system for 3D modeling and application requiring certain accuracies (millimeters to centimeters).